Budaya Literasi sebagai Cara Mewujudkan Institusi Pendidikan yang Berkualitas - Achadi Budi Santosa (Peneliti.net, 2021)
The quality of education is closely related to the literacy culture of the community. The low literacy culture in children is alleged to have been the cause of the low quality of education in Indonesia. The purpose of this study was to determine the role of literacy culture in improving the quality of education, to find out how to increase the literacy culture of students, and to determine the supporting and inhibiting factors in improving the literacy culture of students. The method used in this research is a qualitative approach. The results showed that literacy culture is very influential in education, especially to absorb information and increase the skill level of students. Efforts to increase literacy culture include the Literacy Awareness Movement program and collaborating with various elements to increase literacy awareness.